2021
DOI: 10.3390/ijerph181910013
|View full text |Cite
|
Sign up to set email alerts
|

Retention Rates and the Associated Risk Factors of Turnover among Newly Hired Nurses at South Korean Hospitals: A Retrospective Cohort Study

Abstract: This retrospective cohort study analyzed the turnover rate and the risk factors of turnover among newly hired nurses at tertiary and secondary hospitals in South Korea. Using National Health Insurance Service data, this study created a cohort of 21,050 newly hired nurses across 304 hospitals in 2018, with a follow-up period of 18 months. Retention and turnover risk factors were analyzed at 6-month intervals. Differences in retention period according to hospitals’ organizational characteristics and nurses’ indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
6
1
Order By: Relevance
“…16, and 0.27, respectively and 69% of newly hired employees had never changed their workplace. The turnover rate of 12% for newly hired employees in this study (between the years 2005 and 2006, which was mentioned in the present study) was lower than what Kim & Kim(17)were reported in their study for newly hired nurses at South Korean Hospitals (turnover rate: 26.4%) and the one Park and ko(18)revealed in their study (turnover rate:22%). The turnover rate within two years of employment in the current study was largely similar to the findings of another research with a turnover rate of 17.7% that examined factors related to turnover of new graduate nurses between the years[2006][2007][2008] …”
contrasting
confidence: 75%
“…16, and 0.27, respectively and 69% of newly hired employees had never changed their workplace. The turnover rate of 12% for newly hired employees in this study (between the years 2005 and 2006, which was mentioned in the present study) was lower than what Kim & Kim(17)were reported in their study for newly hired nurses at South Korean Hospitals (turnover rate: 26.4%) and the one Park and ko(18)revealed in their study (turnover rate:22%). The turnover rate within two years of employment in the current study was largely similar to the findings of another research with a turnover rate of 17.7% that examined factors related to turnover of new graduate nurses between the years[2006][2007][2008] …”
contrasting
confidence: 75%
“…Consequently, the turnover rates of new nurses hired between 2017 and 2020 were not included. To clarify, this study does not account for the 26.4% turnover rate of newly hired nurses within their first year of employment in 2018, as reported in a previous study (Kim & Kim, 2021). This previous study was conducted during the same period that turnover rates were tracked in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the dependent variable was nurse turnover. Turnover refers to nurses leaving their current hospital and becoming employed at another clinical institution or leaving the field of clinical nursing (Kim & Kim, 2021). We monitored turnover events at medical institutions throughout the follow-up period.…”
Section: Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study, the risk for turnover in new nurses who worked less than one year was double than that in nurses with more than five years of work experience. Among new nurses, turnover rates within the first and second six months of working was 20.1% and 6.3%, respectively [ 6 ]. More importantly, according to the Hospital Nurses Association, the turnover rates in new nurses increased from 15.4% in 2006 to 45.5% in 2018, illustrating a 30% increase during a 12-year period [ 7 ].…”
Section: Introductionmentioning
confidence: 99%